Systematic Review of the Effects of Second Responder Programs, 1992-2007 - Davis, Robert C. ([Verlag nicht ermittelbar], 2011)
The purpose of this systematic review was to compile and synthesize published and unpublished empirical studies of the effects of second responder programs on repeat incidents of family violence. The researchers employed multiple strategies to search for literature that met the eligibility criteria. A keyword search was performed on a variety of online databases. Researchers reviewed the bibliographies of all second responder studies they located. Researchers performed hand searches of leading journals in the field and searched the Department of Justice Office of Violence Against Women Web site for a listing of federally-funded second responded programs and any evaluations conducted on those programs. A total of 22 studies that discussed second responder programs were found by the research team. Of these, 12 were eliminated from the sample because they did not meet the inclusion criteria, leaving a final sample of 10 studies. After collecting an electronic or paper copy of each article or report, researchers extracted pertinent data from each eligible article using a detailed coding protocol. Two main outcome measures were available for a sufficient number of studies to permit meta-analysis. One outcome was based on police data (Part 1: Police Data, n=9), for example whether a new domestic violence incident was reported to the police in the form of a crime report within six months of the triggering incident. The second outcome was based on survey data (Part 2: Interview Data, n=8), for example whether a new domestic violence incident occurred and was reported to a researcher during an interview within six months of the triggering incident. Several of studies (n=7) included in the meta-analysis had both outcome measures.